АТРАЗИНДИН ТОПУРАКТАН АР КАНДАЙ ЭКСТРАГЕНТТЕР МЕНЕН БӨЛҮНҮП ЧЫККАН ГУМИНДИК ЗАТТАР МЕНЕН ӨЗ АРА АРАКЕТИ (КЫРГЫЗ РЕСПУБЛИКАСЫНЫН УЛУТТУК ИЛИМДЕР АКАДЕМИЯСЫНЫН КАБАРЛАРЫ, 2025)
The fractions of humic substances (HS) of peat soil obtained by extraction by different solvents. They are characterized by differences in the amounts of aliphatic and aromatic carbons of the structures. The isotherms of atrazine sorption on the obtained fractions fractions of HS were studied. It was found that the sorption value, depending on the nature extractant, changed in the following order: acetone > NaOH > DMSO > Na4P2O7, and the reverse order is observed for desorption. The results of the study was indicated that content of aliphatic carbon in the molecular structure of HS is a controlling parameter for sorption. Hydrophilic interactions and conformational flexibility of the aliphatic parts of humic substances structure control of the sorption of atrazine in the volume of self-associated aggregates of humic substances. In contrast, conformational rigidity, caused by the high content of aromatic parts in the structure of humic substances, probably contributes only to surface sorption.